2022
DOI: 10.1186/s12905-022-01775-1
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing factors associated with time to age at first marriage among women in Ethiopia: log logistic-gamma shared frailty model

Abstract: Objective The main objective of this study is to fit Log logistic-Gamma shared frailty model for the determinant of time to age at first marriage among women in Ethiopia. Methods The data set in this study were obtained from Demography and Health survey conducted in Ethiopia in 2016. In this study, we used Log logistic-Gamma shared frailty model to account for the loss of independence that arises from the clustering of women in region of Ethiopia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…This is in line with findings by a systematic review of studies from across Africa that indicated that the odds of first adolescent pregnancy was higher with increasing age [ 6 ]. This may be attributed to a common practice of forcing girls in this age group into early marriages(given that most studies show this age group as the average age of marriage) which exposes them to unsafe sex practices since they are not empowered enough to use contraceptives which increases their chances of getting pregnant [ 32 34 ]. Interestingly and uniquely with this analysis, all teenagers, regardless of their wealth quintile had higher odds of teenage pregnancy compared to their counterparts in the richest quintile.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with findings by a systematic review of studies from across Africa that indicated that the odds of first adolescent pregnancy was higher with increasing age [ 6 ]. This may be attributed to a common practice of forcing girls in this age group into early marriages(given that most studies show this age group as the average age of marriage) which exposes them to unsafe sex practices since they are not empowered enough to use contraceptives which increases their chances of getting pregnant [ 32 34 ]. Interestingly and uniquely with this analysis, all teenagers, regardless of their wealth quintile had higher odds of teenage pregnancy compared to their counterparts in the richest quintile.…”
Section: Discussionmentioning
confidence: 99%